The Account of Spatial Inhomogeneity of the Temperature in the Synergetic Model of Boundary Friction - I.A. Lyashenko; N.N. Manko (Журнал нано- та електронної фізики)
The work presents the further development of the synergetic model describing the state of the ultrathin lubricant film clamped between two atomically smooth solid surfaces operating in the boundary friction mode. The stress distribution over the thickness of lubricant has been obtained and described during the implementation of the numerical procedure for solution of one-dimensional partial differential equation, which will trace the evolution of the tribological system. The stress profiles have been built at the different time moments and the system evolution to the steady state has been shown. The dependence of this state on the temperature has been observed, and it has been shown that the temperature growth causes the increase of the relative shear velocity of the friction surfaces.